TINJAUAN PERLINDUNGAN HAK TUNGGAL PEMEGANG MEREK DAGANG TERKENAL CROCODILE (STUDI PUTUSAN MAHKAMAH AGUNG NOMOR 74 PK/PDT.SUS-HKI/2019) - Bobbie Khoman; Jeane Neltje Saly (Jurnal Hukum Adigama, 2021)
In Law Number 20 of 2016 concerning Marks and Geographical Indications Article 1 Paragraph (5) it has been explained that the right to a mark is an exclusive right granted by the state to the owner of a registered mark for a certain period of time by using the Mark itself or giving permission to another party to use it. However, in the implementation, disputes often occur between parties, especially regarding the rights to this mark. This dispute also raises questions regarding legal protection for trademark rights holders and how the judge's considerations relate to the decision of a trademark dispute. So it’s necessary to study which aspects can be considered as conditions for a mark to be canceled or removed to ensure legal protection for the parties who own the rights to the mark and also in an effort to achieve legal certainty itself. The type of research is normative research. To support this research, the author uses the type of literature study research. The method used is using a statutory approach and a case approach. It turns out that based on the results of the study, it can be seen that the conclusion is the applicable law is sufficient to regulate trademark rights, but it is necessary to reoptimize the application and implementation of this law by the parties concerned. Trademarks as a product of intellectual results of certain parties must be guaranteed and protected by the state, one of which is to advance the country.